Read and Write the Qur’an at Ma’had al-Jami’ah Policy Program, Learning Impact, and Effectiveness - Herlambang, Saifuddin; Cucu, Cucu; Rahmap, Rahmap (Nazhruna: Jurnal Pendidikan Islam, 2024)
This article discusses the reading and writing of the Qur'an policy program at Ma'had al-Jami'ah (College Student Boarding School) IAIN Pontianak. This paper used a type of qualitative research with a phenomenological approach. The author wants to see the effectiveness of implementing the Qur'an reading and writing policy that takes place among students. The respondents or informants in this study are stakeholders of Ma'had al-Jami'ah IAIN Pontianak, be it the rector of IAIN Pontianak, mudir (director) Ma'had al-Jami'ah, educators, and students. Data is obtained through interviews, observations, documentation, and surveys. Data collection through surveys complements interviews, observation, and documentation data. The survey was conducted with all students living in Ma'had al-Jami'ah, IAIN Pontianak. The results of this study show that the policy of reading and writing the Qur'an in Ma'had al-Jami'ah IAIN Pontianak is still oral or appealing. Based on the analysis used by the author indicates that the implementation of reading and writing the Qur'an is quite effective based on the following indicators: 1) program success, as evidenced by an increase in students who initially were in the red zone turning yellow and green. 2) The success of the target is reviewed from the initial filter through the Qur'an reading test in the red category. Following the Qur'an, reading and writing programs are required to be right on target. 3) Satisfaction with the program: the results of the 2022 student survey state that there is satisfaction with the reading and writing Qur'an program. 4) students' reports of the results of reading and writing the Quran prove the input and output levels.